Carbon Storage and Sequestration Potential of Tree Stands in Urban Green Spaces of Kolkata, India - Darshana Tolangay; Sk Sakil Hossain; Saurav Moktan (FORESTIST, 2026)
This study examines tree diversity, biomass, and carbon stock in urban green spaces of Kolkata, India. Ten sites within the study area were chosen for the study. A random sampling method based on canopy cover was employed to enumerate tree species across ten sites, through 50 m °ø 50 m quadrats. A non-destructive approach was used to estimate biomass and total carbon. The results revealed 1141 individual trees, representing 75 species, with Fabaceae as the prominent family. The Shannon diversity index ranged from 2.968 to 3.491, while species richness varied between 2.753 and 3.357. Roystonea regia and Monoon longifolium predominated with stand densities of 92 individuals ha−1 and 69 individuals ha−1, respectively. The basal area of woody species ranged from 9.16 °æ 0.33 to 28.15 °æ 0.74 m©˜ ha−1, with Roystonea regia being a key contributor. Total estimated biomass varied from 197.74 °æ 9.89 Mg ha−1 at Site-10 to 536.76 °æ 14.91 Mg ha−1 at Site-2, equating to carbon stocks of 92.94 °æ 4.65 Mg ha−1 and 252.28 °æ 7.01 Mg ha−1, respectively. An estimated total of 6407.96 °æ 174.50 Mg ha−1 carbon was sequestered across the sites. A significant positive correlation was observed between species diversity and total carbon (p < .05). Principal component analysis indicated that basal area and density are more closely associated with total carbon than other variables. These findings provide a crucial understanding of the role of urban green spaces in Kolkata and build evidence of how urban trees contribute to biodiversity and carbon sequestration. Cite this article as: Tolangay, D., Hossain, S. S., & Moktan, S. (2026). Carbon storage and sequestration potential of tree stands in urban green spaces of Kolkata, India. Forestist, 76, 0025, doi:10.5152/forestist.2026.25025.